2016
DOI: 10.1159/000444641
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Types of Compression Neuropathies in Qena Governorate/Egypt: A Population-Based Survey

Abstract: Background: No epidemiological studies on the prevalence of compressive neuropathy have been undertaken in Arab countries. The aim of the study was to estimate the prevalence of the most common types of compressive neuropathies in Qena governorate/Egypt. Methods: The study was part of a community-based survey carried out to assess the prevalence of neuromuscular disorders among the Qena population. A random sampling of 10 districts, 5,039 inhabitants aged ≥20. There were 3,050 urban residents (60.5%) and 1,989… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…11 Clinically focused community surveys and hospital studies have offered brief insight into the spectrum of NMDs in the Middle East, including studies in Egypt with sparse reporting on a multitude of NMD subtypes. 12 The present study found SMA to be the most frequently occurring NMD (52.8%), followed by DMD and LGMD with frequencies of 22.6 and 18.9%, respectively. This is contrary to the reports that have revealed the prevalence and profiles of NMDs in the region.…”
Section: Discussionsupporting
confidence: 52%
“…11 Clinically focused community surveys and hospital studies have offered brief insight into the spectrum of NMDs in the Middle East, including studies in Egypt with sparse reporting on a multitude of NMD subtypes. 12 The present study found SMA to be the most frequently occurring NMD (52.8%), followed by DMD and LGMD with frequencies of 22.6 and 18.9%, respectively. This is contrary to the reports that have revealed the prevalence and profiles of NMDs in the region.…”
Section: Discussionsupporting
confidence: 52%
“…Fig. ulnar nerve damage even in absence of external traumatic injuries [20,21]. Right hand was predominantly affected-59.3%; however, the involvement of left side was quite high too.…”
Section: Non -Traumatic Injuries (N=195)mentioning
confidence: 98%
“…Tarsal tunnel syndrome is a rare condition with diagnosis seldom established. The condition is more commonly reported in females and can involve any age group [44]. The Tinel sign, which is characteristic of TT syndrome is commonly used in the clinical setting to differentiate the condition from plantar nerve compression [37,38].…”
Section: Clinical Presentation Of Heel Pain Due To Plantar Nerve (Mpn...mentioning
confidence: 99%